An Analysis of Help Seeking Behaviors in a Required First Year Course. Issue 4 (2nd October 2019) - Hvizdak, Erin; Prokosch, Jordan; Johnson, Corey M.
Abstract : The aim of this study is to show student perception of the value of library reference and consultation work in the building of information literacy skills. Using student answers to questions about library research help received in a required first year course, the authors analyzed motivations for use of librarian aid, and the types of assistance sought and that ideally could have been utilized. The authors found students primarily received librarian help with locating books, and that students often believed they would have benefited from more in-depth assistance but did not ask for it.